Syndromic Microphthalmia 9: Role of rapid genome sequencing and novel mutations in STRA6 gene. (March 2022) - Saini, Ashish; Almasarweh, Saleem; Acosta, Stephanie; Jayakar, Parul; Janvier, Michelin; Wong, Terence C.; Salyakina, Daria; Sasaki, Jun
Abstract: Matthew Wood syndrome (MWS) or PDAC syndrome, or Syndromic Microphthalmia 9 (MCOPS9), encompasses a phenotype comprising pulmonary hypoplasia/agenesis, diaphragmatic eventration/hernia, anophthalmia/microphthalmia, and cardiac defects (PDAC). It is a rare autosomal recessive condition with an unfavorable prognosis caused by mutations in the STRA6 (Signaling Receptor and Transporter of Retinol) gene. We report a female neonate with bilateral anophthalmia, right lung hypoplasia, hypoplastic branch pulmonary arteries, and malrotation of right kidney secondary to Syndromic Microphthalmia-9. We also add hitherto undescribed phenotypic features of persistent left superior vena cava draining into a dilated coronary sinus, a partial anomalous pulmonary venous connection of the left pulmonary veins into the persistent left superior vena cava and uterus didelphys. Next-generation whole genome sequencing identified two novel pathogenic mutations in the STRA6, which were inherited from the carrier father (c.1301-6T>A) and the carrier mother (c. 347del), respectively. Although a genotype-phenotype correlation is not well established, the described mutations may be associated with severe congenital cardiac defects. This case highlights the association of ocular abnormalities with a myriad of congenital malformations and the utility of rapid whole-genome sequencing in aiding the diagnosis and prognostic management. Table of contents summary: Syndromic Microphthalmia 9, a rare & fatal genetic condition characterized by anophthalmia, pulmonary hypoplasia, congenital cardiac defects, and severe pulmonary hypertension. Highlights: Syndromic Microphthalmia 9 (MCOPS 9) is a rare autosomal recessive condition due to mutations in STRA 6 on chromosome 15. Phenotype include pulmonary hypoplasia, diaphragmatic hernia, anophthalmia/microphthalmia, congenital cardiac defects. Prognosis is poor due to severe pulmonary hypertension. Rapid whole-genome sequencing is a novel tool to accomplish a prompt diagnosis.